Environmental management practices and engineering science: A review and typology for future research. (23rd January 2014) - Evangelinos, Konstantinos I; Allan, Stuart; Jones, Keith; Nikolaou, Ioannis E
ABSTRACT Current literature describes a number of environmental management practices and cleaner production methods that facilitate different industrial sectors to address their various environmental impacts. The high number of present practices makes their use especially difficult and complicated. This paper aims to shed light on this field by providing a typology of those environmental management practices (such as environmental management systems, environmental indicators assessment methodologies, and cleaner productions methods) and their limitations. It also describes the strengths and weaknesses of using such tools and thoughts for future research. Integr Environ Assess Manag 2014;10:153–162. © 2013 SETAC